Diagnostic potential of circulating cell‐free microRNAs for community‐acquired pneumonia and pneumonia‐related sepsis. Issue 20 (11th September 2020) - Hermann, Stefanie; Brandes, Florian; Kirchner, Benedikt; Buschmann, Dominik; Borrmann, Melanie; Klein, Matthias; Kotschote, Stefan; Bonin, Michael; Reithmair, Marlene; Kaufmann, Ines; Schelling, Gustav; Pfaffl, Michael W.
Abstract: Cell‐free microRNAs (miRNAs) are transferred in disease state including inflammatory lung diseases and are often packed into extracellular vesicles (EVs). To assess their suitability as biomarkers for community‐acquired pneumonia (CAP) and severe secondary complications such as sepsis, we studied patients with CAP (n = 30), sepsis (n = 65) and healthy volunteers (n = 47) subdivided into a training (n = 67) and a validation (n = 75) cohort. After precipitating crude EVs from sera, associated small RNA was profiled by next‐generation sequencing (NGS) and evaluated in multivariate analyses. A subset of the thereby identified biomarker candidates was validated both technically and additionally by reverse transcription quantitative real‐time PCR (RT‐qPCR). Differential gene expression (DGE) analysis revealed 29 differentially expressed miRNAs in CAP patients when compared to volunteers, and 25 miRNAs in patients with CAP, compared to those with sepsis. Sparse partial‐least discriminant analysis separated groups based on 12 miRNAs. Three miRNAs proved as a significant biomarker signature. While expression levels of miR‐1246 showed significant changes with an increase in overall disease severity from volunteers to CAP and to sepsis, miR‐193a‐5p and miR‐542‐3p differentiated patients with an infectious disease (CAP or sepsis) from volunteers. Cell‐free miRNAs are potentially novel biomarkers for CAP and may help to identify patients at risk for progress to sepsis, facilitating early intervention and treatment.